Bangladesh : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bangladesh. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the Bangladesh economy continues to perform well with robust and stable growth. The strong growth comes with stable inflation, moderate public debt, and greater resilience to external shocks. The country continues to make steady progress in reducing poverty and improving social indicators. Real GDP growth in FY2017 (ending September 30) further accelerated to 7.3 percent from 7.1 percent in the previous fiscal year. The macroeconomic situation is expected to remain robust in FY2018. Growth is projected at about 7 percent with strong domestic demand. Inflation is expected to remain below 6 percent, close to Bangladesh Bank's target as flood-related pressure on food prices eases with the rice harvest recovery.